Moments of Rupture: Narratological Readings of Contemporary German Literature - Albiero, Olivia (My University, 2016)
“Moments of Rupture: Narratological Readings of Contemporary German Literature” explores the representation of disruptive moments in contemporary German novels using a narratological framework of analysis. Joining the larger conversation on narrative practices in contemporary German literature, the dissertation focuses on key questions of literary form, narration and storytelling in four major novels published at the beginning of the twenty-first century: Christoph Ransmayr’s Der fliegende Berg (2006), Wolfgang Herrndorf’s Sand (2011), Lutz Seiler’s Kruso (2014) and Saša Stanišić’s Vor dem Fest (2014). The project investigates the use of narrative elements to relate, mend and overcome moments of personal, hermeneutical, political and social rupture. By drawing on influential works of narratology, from Aristotle’s early narratology to pertinent contemporary theories (e.g. Bakhtin, Brooks, Fludernik, Genette, Phelan), my study shows how narratives shape and are in turn shaped by the ruptures they describe. Chapters are organized around key narrative categories, which serve to explore one literary text. The opening chapter discusses the significance of time and space in Der fliegende Berg. It shows how a moment of personal rupture is reflected in the transitions between physical, virtual and mythological times and spaces, and in the encounters that characterize them. Chapter two investigates the plotting of Sand. It examines the tension between (re)cognition and mistakes, between understanding and utter bafflement both on the level of diegesis and of reading. Chapter three examines the characters in Kruso. It shows how the relationship between the main figures translates into a political allegory, which stands for the failure of a utopian project and the fall of the Berlin Wall. The final chapter explores the features of the plural voice in Vor dem Fest and its role in preserving a post-socialist community affected by slow decline and the death of its storyteller.
Thesis (Ph.D.)--University of Washington, 2016-08
Keywords: contemporary German literature; narratology; rupture; storytelling; twenty-first century; German literature; german